2011
DOI: 10.1002/chem.201101550
|View full text |Cite
|
Sign up to set email alerts
|

Unified Syntheses of Cavicularin and Riccardin C: Addressing the Synthesis of an Arene Adopting a Boat Configuration

Abstract: Concise syntheses of the natural products cavicularin (ten steps) and riccardin C (seven steps) are reported. Key features of the new synthetic route are a convergent strategy to assemble acyclic precursors and a sequence of regioselective reduction and halogenation steps to facilitate Wittig macrocyclisation and transannular ring contraction reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 52 publications
1
28
0
1
Order By: Relevance
“…Drawing on previous experience,, we identified arenes 16 – 19 as the key building blocks required for our synthesis, as all but arene 17 were commercially available compounds (Scheme ). Moreover, the synthesis of 17 from catechol 13 was readily achieved by a sequence of benzylation, triflation, and Wittig methylenation using standard protocols.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Drawing on previous experience,, we identified arenes 16 – 19 as the key building blocks required for our synthesis, as all but arene 17 were commercially available compounds (Scheme ). Moreover, the synthesis of 17 from catechol 13 was readily achieved by a sequence of benzylation, triflation, and Wittig methylenation using standard protocols.…”
Section: Resultsmentioning
confidence: 99%
“…The largest familial group is based on macrocyclic core 2 , and has riccardin C ( 10 ) at its helm (Figures and ) , . A popular synthetic target for many years, riccardin C recently gained prominence when a screening seeking new leads against cardiovascular disease revealed that it acted as an agonist for the cholesterol‐regulating liver X receptor LXRα and an antagonist for LXRβ . Indeed, it has been tested in many pharmacological screenings,, and these have revealed antifungal[4b] and antibacterial activities, and cytotoxic activity against various cancer cell lines .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Riccardin C ( 96 ) is a macrocyclic bis-bibenzyl entity with pharmacological properties, including antimycotic and antibacterial effects, and cytotoxicity against P-388 mouse leukaemia and KB cell lines from nasopharyngeal carcinoma . In view of these useful medicinal properties Harrowven and co-workers [ 115 ] have reported the synthesis of this molecule by using the McMurry reaction. Kawase and co-workers [ 116 ] have reported double-helically twisted macrocycles 97 exhibiting chiral sensor properties.…”
Section: Reviewmentioning
confidence: 99%
“…[1][2][3][4] These compounds have characteristic structures, and exhibit diverse biological activities, [5][6][7][8][9][10][11][12] and so there is great interest in the synthesis of these compounds and their analogs. [13][14][15][16][17][18][19][20] We recently reported that riccardin-class macrocyclic bis-(bibenzyl)-type phenolic compounds, such as riccardin C (1), exhibit potent antibacterial activity towards methicillin-resistant Staphylococcus aureus (anti-MRSA activity), comparable to that of clinically used drugs, such as vancomycin and linezolid. 21,22 In order to understand the structure-activity relationship of riccardin-C class bis(bibenzyl)s, we previously prepared several riccardin C derivatives, and found that the number and position of hydroxyl group(s) on the benzene ring are important for anti-MRSA activity.…”
Section: Introductionmentioning
confidence: 98%